Effect Event, Word of Mouth, Direct Marketing on Purchase Decision Le-Fluffy Dessert - Setiyono, I.V.; Dewi, L. (Review of Management and Entrepreneurship, 2017)
Le-Fluffy Dessert is a food and beverage company that offers pudding and milk made from soy and milk without preservatives. This study aims to determine the influence of events, word of mouth, direct marketing on purchasing decision. This research used a quantitative approach, with population including Le-Fluffy Dessert’s consumers buying the products more than twice. Slovin formula was used to obtain 74 samples. The independent variables in this research were events, word of mouth, and direct marketing. The dependent variable in this research was consumen purchasing decision. The method of data collection in this research was questionnaire with Likert scale measurement. Analysis tool of this research is multiple linear regression. The event, word of mouth, direct marketing have a significant positive effect on consumer purchasing decision of Le-Fluffy Dessert.